Peranan Pemerintah Desa Dalam Pengembangan Desa Wisata Di Desa Tunjungan Kecamatan Tunjungan, Kabupaten Blora - Rahmad Purwanto W; Chistine Diah W (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
The aim of this research is to describe the role of village government in developing tourist villages. The village government formulates policies for village development and facilitates the development of tourist villages by utilizing village potential, especially natural recreation, water tourism and fishing in the Ngreneng Reservoir, Cemara Pitu hill, Greneng Peak, Nglawungan Durian Garden, Pak Nari Fruit Farm, Asri Gardens and Fruit Gardens. and recreational activities such as outbound, gatherings, activities in the field, group exercise and culinary delights at tourist locations. The village government ratifies the plan to develop a tourist village, forms a tourism management and clean water facilities, toilets and parking lots and creates public order at tourist sites.